Climate Change Mitigation and Disaster Preparedness in Indonesia’s Outermost Islands (Jurnal Lemhannas RI, 2025)
Purpose: This study aims to analyse the governance of climate change responses on Indonesia's outermost islands, using Miangas Island as a strategic case study. The analysis evaluates the role of climate adaptation in strengthening disaster preparedness and national resilience amidst environmental threats and the vulnerabilities inherent to border regions.Study Design/Methodology/Approach: A qualitative descriptive case study approach integrates document analysis, policy analysis, and a SWOT matrix. Baseline data, regulations, official reports, and international climate databases were analysed using socio-ecological systems theory, adaptive governance, the Sendai Framework, and the Asta Gatra model of national resilience. This framework encompasses Tri Gatra as natural aspects and Panca Gatra as social aspects of national resilience.Findings: Miangas faces biophysical vulnerabilities due to its limited land area, low elevation, rising temperatures and sea levels, and coastal abrasion. Disaster preparedness is further constrained by the absence of integrated early warning systems and limitations in evacuation infrastructure, trained personnel, and transportation access. The Asta Gatra analysis shows that pressures on Tri Gatra can affect Panca Gatra through disruptions to livelihoods, public services, population mobility, and border security. Social capital, the mapalus tradition, Miangas's strategic location, and policy support strengthen the community's adaptive capacity.Originality/Value: This article positions the outermost island as a strategic space that links climate adaptation, environmental resilience, disaster preparedness, territorial integrity, sovereignty, and national security within the Asta Gatra framework.